Erythropoietin attenuates LPS-induced microvascular damage in a murine model of septic acute kidney injury - Stoyanoff, Tania Romina (2018)
Fil: Stoyanoff, Tania Romina. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas Naturales y Agrimensura; Argentina.